Freeze Concentration, Supercooling, and Glass Formation in Perchlorate and Chlorate Brines: Habitability in Salty Martian Ice - Ardith Bravenec; David C. Catling (The Planetary Science Journal)
Oxychlorine salts, including chlorates and perchlorates, are widespread in Martian soil. Despite this significance, key metrics influencing the rheological properties and habitability of aqueous oxychlorine systems, such as the glass transition temperature ( T _g ), degree of supercooling, critical concentrations, and maximum freeze concentrations, remain poorly characterized. This study employs differential scanning calorimetry to measure the properties of supercooled aqueous solutions of Ca, Mg, and Na chlorate brines. We systematically quantify the effects of initial brine composition, concentration, and cooling or warming rates. Our results demonstrate that brines with concentrations exceeding the eutectic concentration readily supercool and vitrify at various cooling rates, whereas those below the eutectic concentration partially freeze. In these mixed-phase ice-brine systems, we quantify the fraction of water ice and glass phases formed from freeze concentration, along with the concentration of residual brine for both perchlorates and chlorates. Increased cooling rates favor supercooling and glass formation over ice formation, though the residual liquid concentration is minimally affected, indicating that initial solution concentration is the primary control factor. Even under equilibrium ice formation, the residual liquid phase can exhibit metastable behavior. The glass-forming ability is greatest for perchlorate anions and weakest for chloride anions, following the trend ClO _4 ^– > ClO _3 ^– > Cl ^– . Among cations, Mg ^2+ and Ca ^2+ show a greater propensity for glass formation compared to Na ^+ . These findings enhance our understanding of liquid stability and metastability on Mars, supporting the potential for supercooled salty waters to persist as interconnected brine networks or nodes interspersed among ice grains.